TREATMENT OF GINGIVAL HYPERPLASIA INDUCED BY NIFEDIPINE - Mitayani Restuning Kusumarini; Dewi Nurul Mustaqimah (Faculty of Dentistry, Universitas Indonesia, 2015)
The use of Nifedipine as cardiovascular therapy is proven to be the cause of gingival hyperplasia. The objective of this present case is to report the gingival hyperplasia induced by nifedipine, and the best management suggested. In both cases, the substitution of nifedipine by another drug and intensive oral hygiene procedure could eliminate the gingival hyperplasia.